Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Wednesday, March 27, 2013 at 11:58am.

- Algebra -
**Steve**, Wednesday, March 27, 2013 at 12:24pmd = √(4+(y-5)^2) + √(9+(y-9)^2)

dd/dy = (y-5)/√(4+(y-5)^2) + (y-9)/√(9+(y-9)^2)

= [(y-9)√(4+(y-5)^2) + (y-5)√(9+(y-9)^2)]/(√(4+(y-5)^2) * √(9+(y-9)^2))

dd/dy=0 when

(y-9)√(4+(y-5)^2) + (y-5)√(9+(y-9)^2) = 0

y = 33/5

a+b=38

**Related Questions**

Maths - The value of y that minimizes the sum of the two distances from (3,5) to...

Geometry - The value of y that minimizes the sum of the two distances from (3,5...

Geometry - The value of y that minimizes the sum of the two distances from (3,5...

Algebra - Let \phi(n) be the Euler Phi Function. If 1 \leq n \leq 1000, what is ...

Math - Let ϕ(n) be the Euler Phi Function. If 1≤n≤1000, what is...

Algebra - Let S(N) denote the digit sum of the integer N. Let M denote the ...

Econ - A result of welfare economics is that the equilibrium price of a product ...

Algebra - The sum of three consecutive integers is a multiple of 89 and is a ...

Math - The least squares regression line is a unique line for each data set. ...

algebra - The sum of an uncirculated 'Mint-65 '1950 jefferson nickkle mintedd in...